2011
DOI: 10.1002/jtr.1864
|View full text |Cite
|
Sign up to set email alerts
|

‘How's the Service?’ A Study of Service Quality Perceptions across Sectors and Source Markets

Abstract: This study assessed the performance of the hotel, retail and travel agency sectors in Hong Kong. The importance–performance analysis (IPA) model and various statistical techniques were employed to examine visitors’ cognition of the importance and performance of pertinent service quality attributes and to better understand the factors that may influence their overall satisfaction across different sectors and source markets. Whereas the multivariate analysis of variance and analysis of variance tests suggest no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Luego de ello, con el fin de prevenir sesgar la inclusión/exclusión de estudios, se seleccionaron los 10 primeros trabajos que ofreció Scopus (17.8% de la población delimitada) y, con base en ellos, prosiguió la exploración. De nuevo China participó notablemente en el grupo de estudios explorados (Pornpitakpan y Han, 2013;Ayeh y Chen, 2013;Lee et al, 2013). También se encontraron esfuerzos por ampliar el alcance de las investigaciones hacia otros contextos, independiente de la tipología de servicios, como se identificó en el ELR; por ejemplo, Oyewole (2013) enfocó la evaluación de la calidad del servicio haciendo hincapié en consumidores afroamericanos (características socioeconómicas y demográficas) manifestando que existen pocos estudios sobre su actitud y comportamiento hacia el consumo, en este caso en restaurantes tipo buffet.…”
Section: Discussionunclassified
“…Luego de ello, con el fin de prevenir sesgar la inclusión/exclusión de estudios, se seleccionaron los 10 primeros trabajos que ofreció Scopus (17.8% de la población delimitada) y, con base en ellos, prosiguió la exploración. De nuevo China participó notablemente en el grupo de estudios explorados (Pornpitakpan y Han, 2013;Ayeh y Chen, 2013;Lee et al, 2013). También se encontraron esfuerzos por ampliar el alcance de las investigaciones hacia otros contextos, independiente de la tipología de servicios, como se identificó en el ELR; por ejemplo, Oyewole (2013) enfocó la evaluación de la calidad del servicio haciendo hincapié en consumidores afroamericanos (características socioeconómicas y demográficas) manifestando que existen pocos estudios sobre su actitud y comportamiento hacia el consumo, en este caso en restaurantes tipo buffet.…”
Section: Discussionunclassified
“…The widely used SERVQUAL instrument, for example, which is a 22-item, five-dimension scale (Parasuraman et al, 1985, 1988), applies mostly to short-term service encounters such as the office-based services provided by travel agencies, hotels and airlines (Fick and Ritchie, 1991; Lam and Zhang, 1999; LeBlanc, 1992) and may not capture the most salient dimensions of GPTs. As such, attempts to force SERVQUAL onto the multiple service encounters of Chinese GPT services have necessarily involved significant changes to the original instrument (Ayeh and Chen, 2013; Chang, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surprisingly little research has been undertaken on service quality of Chinese GPTs either in general or specifically in the Australian context. In the broader business and tourism contexts, demand for quality service has become clear for business operators in general (Schwartz, 2007; Ting, 2004; Velázquez et al, 2011) and specifically for tourism stakeholders (Ayeh and Chen, 2013; Mak et al, 2011). To achieve long-term profit and business sustainability, Chinese tour operators need to have a quality service–based orientation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors (Cheng et al, 2012;Mosavi & Ghaedi, 2012;Ryu & Han, 2011;Wall & Berry, 2007) have reported that physical evidences have a different impact on guests who are visiting the restaurant for the Marketing a obchod fi rst time (i.e., fi rst-time buyers) than on guests who have already visited the restaurant in the past. In particular, factors associated with cleanliness and noise signifi cantly infl uence guests' perception of quality (Barber et al, 2011;Barber & Scarcelli, 2010). According to fi ndings presented in this section and based on several quality models (SERVQUAL, DINESERV, Tangserv, SERVPERF), we have included the following quality factors in our questionnaire: cleanliness of the premises, neat and presentable staff, comfort, design in accordance with food offering, and sense of security.…”
Section: Physical Evidencementioning
confidence: 99%
“…Despite the importance of food quality, some scholars have focused on the service encounter aspect of service quality (Ayeh & Chen, 2013;Edvardsson, 2005;Han, Back, & Barrett, 2010). Further examination reveals that most studies (Andaleeb & Conway, 2006;Barber, Goodman, & Goh, 2011;Mosavi & Ghaedi, 2012;Raajpot, 2002;Voon, 2012) have empirically investigated the role of different and specifi c quality factors, such as environment, tangibles, cleanliness, price perception, and so forth. One interesting fi nding that emerges from the comparison of these studies is that research results are mutually inconsistent, as they emphasize the importance of different quality factors.…”
Section: Introductionmentioning
confidence: 99%